The Relationship of Family Support with Adaptation to Psychological Changes in Public - Rina Anggraini Damanik; Nadya Fitriani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Postpartum is the period that begins after the birth of the placenta and ends when the bladder returns to its original state before pregnancy, which lasts for 6-40 days. The length of the postpartum period is ± 6 – 8 weeks. The postpartum period begins after the birth of the placenta and ends when the uterine organs return to their pre-pregnancy state, which lasts approximately 6 weeks. The aim is to determine the relationship between family support and adaptation to psychological changes in postpartum mothers. Research Method uses a quantitative approach with correlation methods and a cross sectional approach. The sampling technique was purposive sampling technique, the number of respondents was 35 respondents. The research location was at the Romana Tanjung Anom Clinic which was carried out from January 5 to March 30 2024. Data analysis using Chi Square. The result was that 74.3% of 26 respondents were in the category of supporting postpartum mothers. Univariate Analysis of Adaptation to Psychological Changes in Pregnant Women found that the majority of postpartum mothers were in the positive psychological adaptation category with 27 respondents or 77.1%. Bivariate analysis obtained a p-value of 0.000. The conclusion is that there is a relationship between family support and adaptation to psychological changes in postpartum mothers.